Radiation exposure to nuclear medicine technologists performing a V/Q PET: Comparison with conventional V/Q scintigraphy, [18F]FDG PET and [68Ga]Ga DOTATOC PET procedures - Blanc-Béguin, Frédérique; Damien, Pascal; Floch, Romain; Kerleguer, Kévin; Hennebicq, Simon; Robin, Philippe; Salaün, Pierre-Yves; Le Roux, Pierre-Yves (Frontiers in Medicine, 2022)
ABSTRACT Ventilation/Perfusion (V/Q) PET/CT is an emerging imaging modality for regional lung function evaluation. The same carrier molecules as conventional V/Q scintigraphy are used but they are radiolabelled with gallium-68 (68Ga) instead of technetium-99m (99mTc). A recurrent concern regarding V/Q PET imaging is the radiation dose to the healthcare workers. The aim of this study was to evaluate the total effective dose and the finger dose received by the technologist when performing a V/Q PET procedure, and to compare them with the radiations doses received with conventional V/Q scintigraphy, FDG PET and Ga DOTATOC PET procedures. Materials and methods The whole body dose measurement was performed 10 times for each of the evaluated procedures using an electronic personal dosimeter (ED). For V/Q PET and V/Q scintigraphy procedures, ventilation and perfusion stages were separately evaluated. Internal exposure was measured for ventilation procedures. Finger dose measurements were performed 5 times for each of the PET procedures using Thermoluminescence (TL) pellets. Results The technologist effective dose when performing a V/Q PET procedure was 2.83 ± 0.67 µSv, as compared with 1.16 ± 0.34 µSv for conventional V/Q scintigraphy, 2.13 ± 0.77 µSv for [68Ga]Ga-DOTATOC, and 2.86 ± 1.79 µSv for FDG PET procedures, respectively. The finger dose for the V/Q PET procedure was similar to the dose for a [68Ga]Ga-DOTATOC scan (0.35 mSv and 0.32 mSv, respectively). Conclusion The technologist total effective dose for a V/Q PET procedure is approximately 2.4 higher than the dose for a conventional V/Q scintigraphy, but in the same range than the radiation exposure when performing common PET procedures, both in terms of total effective dose or finger dose. These results should be reassuring for the healthcare workers performing a V/Q PET procedure.